COMPUTER APPLICATION MODEL TO SIMU-LATE THE LAND USE CHANGE SCENARIO. (A CASE STUDY IN UPPER CILIWUNG WATERSHED, BOGOR, WEST JAVA, INDONESIA) (Eng.) - Asep Denih (Ilmu Komputer, FMIPA, Universitas Pakuan, 2006)
KOMPUTASI, Juli 2006, Vol.3, No.6, Hal 1-11In general, any geographic phenomena are visually depicted as ‘static’ spatial model. This thesis presents how some variable can be combined to give more information to the spatial analysis model and how to implement the dynamic map and the dynamic spatial model.. Conceptually, there are six steps to implement the dynamic spatial model for Upper Ciliwung Watershed including data compilation and preparation, data analysis, spatial model development, interfacing, spatial database programing, simulation and verification. Microsoft Visual Basic V.6.0 and Map Object Version 2.1 were used to implement. The application program developed is generally interactive with a few tools and dialog interface. User can flexibly set up different land use change scenarios for knowing the hydrology responses to support the decision maker. The outputs of the dynamic spatial analysis model are: peak runoff rate [m3/s]. runoff volume [m3], and percentage of each contributing area. This dynamic spatial analysis model is able to determine of contributing area of runoff water by tracking the flow direction of its watershed characteristic from the study area. The result of this dynamic spatial analysis model will be useful to be use for controlling the impact of the land use changes od Upper Ciliwung Watershed. Key Word: Spatial analysis, dynamic model, land use change, scenario, peak run off rate, debit, watershed